Role of the Neutrophil to Lymphocyte Ratio in Guillain Barré Syndrome: A Systematic Review and Meta-Analysis - Shirin Sarejloo; Shokoufeh Khanzadeh; Samaneh Hosseini; Morad Kohandel Gargari; Brandon Lucke-Wold; Seyedarad Mosalamiaghili; Pouria Azami; Sanaz Oftadehbalani; Shahram Sadeghvand (Mediators of Inflammation)
In this study, we conducted a systematic review and meta-analysis regarding the role of the neutrophil to lymphocyte ratio (NLR) in Guillain Barré syndrome (GBS). The most recent update to the search was on July 18, 2022, through the databases of Web of Science, PubMed, Embase, and Scopus. The Newcastle-Ottawa scale was used for quality assessment of included studies. Finally, 14 studies were included in the review, and among them, ten studies were included in the meta-analysis. Our results showed that NLR levels were significantly increased in the patients with GBS compared with healthy controls (SMD=1.05; 95%CI=0.59 to 1.50, P<0.001). After treatment, NLR levels were decreased to the extent that they became similar to healthy controls (SMD=−0.03, 95%CI=−0.29 to 0.22, P=0.204). Moreover, NLR was a stable predictor of outcome or response to treatment in such patients (SMD=1.01, 95%CI=0.65 to 1.37, P<0.001); the higher the NLR, the worse the outcome. In addition, patients who underwent mechanical ventilation had higher levels of NLR compared to those who did not (SMD=0.93, 95%CI=0.05 to 1.82, P=0.03). However, NLR levels were not different among distinct GBS subtypes, so it could not distinguish among them. In conclusion, our analysis indicates that the NLR levels are highly elevated in patients with GBS. Therefore, the NLR has the potential to be used as a biomarker to inform diagnosis, prognosis, or treatment responses in GBS, and future studies are warranted.